Pengaruh Pengetahuan dan Perilaku Petani dalam Memelihara Saluran Irigasi di Desa Kunjeng Kecamatan Gubug Kabupaten Grobogan - Aninditya, Destiana; Banowati, Eva; Sriyanto, Sriyanto (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2020)
Irrigation is used to facilitate the irrigation of agricultural land. In an effort to maintain irrigation canals farmersshould have knowledge about irrigation in order to encourage the behavior of maintaining irrigation channels.This study aims to: 1) determine the knowledge of farmers in maintaining irrigation channels; 2) know thebehavior of farmers in maintaining irrigation channels; 3) analyze the influence of farmers' knowledge andbehavior in maintaining irrigation channels. The results showed that farmers 'knowledge significantly influencedfarmers' behavior in maintaining irrigation channels. Because the results of the hypothesis test is known tocalculate 11.527. Based on the calculation of the test results of the determination of the value of R square = 0.639,this shows that the magnitude of the effect given by the independent variable on the dependent variable is 63.9%.Farmers' knowledge is classified as good criteria with an average of 72.18%, while the behavior of farmers tomaintain irrigation channels is classified as sufficient criteria with an average score of 68.58%. For the regressionresults it is known that the knowledge variable gives an effect of 0.8 on the behavior variable. Irigasi digunakan untuk mempermudah dalam pengairan lahan pertanian. Dalam upayamemelihara saluran irigasi petani seharusnya memiliki pengetahuan tentang irigasi supayamendorong perilaku memelihara saluran irigasi. Penelitian ini bertujuan: 1) mengetahuipengetahuan petani dalam memelihara saluran irigasi; 2) mengetahui perilaku petani dalammemelihara saluran irigasi; 3) menganalisis pengaruh pengetahuan dan perilaku petani dalammemelihara saluran irigasi. Hasil penelitian menunjukkan bahwa pengetahuan petani berpengaruhsignifikan terhadap perilaku petani dalam memelihara saluran irigasi. Karena hasil uji hipotesisdiketahui nilai t hitung sebesar 11,527. Berdasarkan perhitungan hasil uji determinasi nilai R square=0,639, hal ini menunjukkan bahwa besarnya pengaruh yang diberikan variabel independentterhadap variabel dependent sebesar 63,9%. Pengetahuan petani tergolong dalam kriteria baikdengan rata-rata 72,18%, sedangkan untuk perilaku petani memelihara saluran irigasi tergolongdalam kriteria cukup dengan rata-rata skor 68,58 %. Untuk hasil regresi diketahui bahwa variabelpengetahuan memberikan pengaruh sebesar 0,8 terhadap variabel perilaku.